Reflection of the traditions and customs of the Kazakh girl in the context of «Language-Culture-Society» - Abdimaulen Г. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
The article highlights the features of the customs and traditions of the Kazakh people, dedicated to the girl. The character of the national idea of the girl, recorded in the phraseological fragments of the worldview of the Kazakh people, is illustrated in the context of «Language-Culture-Society». The purpose of the article is to skillfully acquaint future generations with the attitude of the Kazakh people to traditions and their values using phraseological expressions. A girl grows up free and carefree in any Kazakh family. The nature of girls is very gentle, charming, and beautiful. Girls grow up with such good qualities thanks to traditions and customs. Parents taught their daughters from an early age to be smart, resourceful, calm and patient. They explained that these qualities help them achieve great success in their future life. Kazakhs perceived their daughters as ambassadors connecting the two countries. A married girl reflects her country through her character and upbringing, so the Kazakhs paid great attention to the upbringing of their daughters. The duty and main goal of every parent are to marry their daughter with honor to a loved one when she reaches the appropriate age. It is taken into account that all actions taken do not go beyond the framework of customs and traditions in achieving these goals. The research is aimed at a deeper disclosure of everyday and forgotten traditions of the Kazakh people in relation to girls. Phraseological turns of phrase characterize the spiritual beauty and dignity of a girl.